2003
DOI: 10.1074/jbc.m309016200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Locus and Structural Characterization of the Biochemical Defect in the O-Antigenic Polysaccharide of the Symbiotically Deficient Rhizobium etli Mutant, CE166

Abstract: The O-antigen polysaccharide (OPS) of Rhizobium etli CE3 lipopolysaccharide (LPS) is linked to the core oligosaccharide via an N-acetylquinovosaminosyl (QuiNAc) residue. A mutant of CE3, CE166, produces LPS with reduced amounts of OPS, and a suppressed mutant, CE166 alpha, produces LPS with nearly normal OPS levels. Both mutants are deficient in QuiNAc production. Characterization of OPS from CE166 and CE166 alpha showed that QuiNAc was replaced by its 4-keto derivative, 2-acetamido-2,6-dideoxyhexosyl-4-ulose.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Their normal expression and structures are essential for successful symbiotic infection (8,15,26,31,33,34,49,58). In the present study, we show that the flavonoid-inducible polysaccharide is a rhamnan O antigen, covalently linked to a structurally modified core oligosaccharide lipid A (thus, an LPS).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Their normal expression and structures are essential for successful symbiotic infection (8,15,26,31,33,34,49,58). In the present study, we show that the flavonoid-inducible polysaccharide is a rhamnan O antigen, covalently linked to a structurally modified core oligosaccharide lipid A (thus, an LPS).…”
mentioning
confidence: 71%
“…Previous studies with R. etli and Rhizobium leguminosarum have shown that LPS mutants, containing specific structural defects in the O-antigen portion of their LPSs, are unable to maintain or establish a normal nitrogen-fixing symbiosis with their legume hosts, yielding either Nod ϩ Fix Ϫ or Nod Ϫ Fix Ϫ phenotypes (15,(34)(35)(36). In these cases, a correct LPS structure and normal surface abundance appear to be necessary, even after the initial stages of symbiotic infection (e.g., root hair curling and infection thread formation).…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that the unusual keto sugars that characterize the S. saprophyticus CP structure result from the truncated and presumably dysfunctional capL Ssp gene, encoding a putative reductase enzyme. Similarly, a symbiotic mutant of Rhizobium etli carrying a Tn5 insertion in a putative reductase gene expressed a 2-acetamido-2,6-dideoxy-4-ketohexose rather than N-acetylquinovosamine in the outer core region of its lipopolysaccharide (8). Other examples of bacterial polysaccharides containing a 4-keto hexose (2-acetamido- FIG.…”
Section: Discussionmentioning
confidence: 99%
“…It was furthermore demonstrated that not only the presence of the O-chain polysaccharide on the LPS but also the abundance of O-chain polysaccharide was important for nodulation. For example, mutant strain R. etli CE166 produced, based on PAGE analysis of the LPS, only 40% LPS containing the O-chain polysaccharide compared with the parent strain, and the symbiotic phenotype of this mutant was the same as that observed for a mutant that entirely lacks the O-chain polysaccharide (7,8).…”
mentioning
confidence: 99%